A Methodological Basis for Assessing the Cost-Effectiveness of Corporate Training. Issue 7 (3rd July 2017) - Lapidus, L.; Kazakov, V.
Abstract : The article discusses the methodological aspects of training personnel that will allow specialists in the field of human resources development to plan for the results of training, monitor the educational process, and motivate company employees for training.